Phosphorus Reduces Negative Effects of Nitrogen Addition on Soil Microbial Communities and Functions - Xia, Zongwei; Yang, Jingyi; Sang, Changpeng; Wang, Xu; Sun, Lifei; Jiang, Ping; Wang, Chao; Bai, Edith (Microorganisms (Basel), 2020)
Increased soil nitrogen (N) from atmospheric N deposition could change microbial communities and functions. However, the underlying mechanisms and whether soil phosphorus (P) status are responsible for these changes still have not been well explained. Here, we investigated the effects of N and P additions on soil bacterial and fungal communities and predicted their functional compositions in a temperate forest. We found that N addition significantly decreased soil bacterial diversity in the organic (O) horizon, but tended to increase bacterial diversity in the mineral (A) horizon soil. P addition alone did not significantly change soil bacterial diversity but mitigated the negative effect of N addition on bacterial diversity in the O horizon. Neither N addition nor P addition significantly influenced soil fungal diversity. Changes in soil microbial community composition under N and P additions were mainly due to the shifts in soil pH and NO3− contents. N addition can affect bacterial functional potentials, such as ureolysis, N fixation, respiration, decomposition of organic matter processes, and fungal guilds, such as pathogen, saprotroph, and mycorrhizal fungi, by which more C probably was lost in O horizon soil under increased N deposition. However, P addition can alleviate or switch the effects of increased N deposition on the microbial functional potentials in O horizon soil and may even be a benefit for more C sequestration in A horizon soil. Our results highlight the different responses of microorganisms to N and P additions between O and A horizons and provides an important insight for predicting the changes in forest C storage status under increasing N deposition in the future.